PENGARUH PERSEPSI HARGA, PERAN INSENTIF PEMERINTAH, DAN KETERSEDIAN STASIUN PENGISIAN KENDARAAN LISTRIK UMUM (SPKLU) TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN LISTRIK KOTA SEMARANG - Atthariq, Adlan Jingglang; Puspitasari, Diana; Panjaitan, Roymon; Anomsari, Ariati (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
The transport industry is growing rapidly, creating intense competition and driving the adoption of eco-friendly electric vehicles to reduce pollution. In Indonesia, despite the large market, electric vehicle adoption is still limited. This study in Semarang City evaluated the factors influencing the decision to purchase an electric vehicle, focusing on perceived price, government incentives, and SPKLU availability using a quantitative survey and multiple regression analysis distributed via Googleform then the data was processed using SPSS 25 and the results showed that perceived price and SPKLU availability had a positive and significant effect, while government incentives had no significant effect. This research recommends increasing the effectiveness of incentive programs and developing charging infrastructure to support the adoption of electric vehicles.